Prevention and Therapy of Experimental Venous Thrombosis in Rabbits by Desmin 370 - Colucci, Mario; Rossiello, Maria Rosaria; Barbanti, Miriam; Calanni, Fiorella; Semeraro, Nicola (Thrombosis and Haemostasis, 1998)
Desmin 370 (D370), a low molecular weight dermatan sulfate, has been shown to reduce the size of preformed thrombi in rats, via a mechanism largely independent of its anticoagulant activity. In the present study we investigated the therapeutic efficacy of D370 in rabbits with experimental jugular vein thrombosis. Experiments performed to evaluate the antithrombotic dosages in rabbits indicated that D370 prevented the formation of venous thrombi (Wessler model) in a dose-dependent manner with complete inhibition at 20 mg/kg. When injected to rabbits bearing a 30 min aged thrombus, D370 caused a time- and dose-dependent reduction in thrombus weight. Thrombi harvested 2 h after injection of 50 mg/kg of D370 were 71% smaller than thrombi from saline-treated rabbits and 50% smaller than pretreatment thrombi, suggesting a double effect of the drug: inhibition of thrombus accretion and reduction of the existing thrombus. Interestingly, pretreatment with the fibrinolytic inhibitor EACA (1 g/kg), significantly attenuated the therapeutic efficacy of D370, suggesting a possible involvement of the fibrinolytic system. Heparin (50 and 200 U/kg) was less active as therapeutic agent, the maximal decrease in thrombus weight, as compared to untreated rabbits, amounting to 38%. Heparin, moreover, caused a more pronounced prolongation of APTT than comparable antithrombotic dosages of D370. Our present data extend previous results on the therapeutic efficacy of D370 and underscore its potential as an alternative antithrombotic drug.